Satisfaction Level of Patients Wearing Removable Dental Prosthesis According to Oral Health Index Profile-14 (Medical Forum Monthly, 2021)
Objective: To determine the level of satisfaction of patients using removable dental prosthesis according to Oral health index profile-14(OHIP-14).Study Design: Cross-sectional descriptive studyPlace and Duration of Study: This study was conducted at the Rehmat Memorial Dental Hospital, Women Medical Dental College Abbottabad, from June 2019 to Feb 2020.Materials and Methods: A total of 207 both genders, with ages ranging between 20 to 70 years, wearing acrylic removable dentures for at least one year, and no signs of pathology in remaining natural teeth were included. Patients wearing cast partial dentures, with defects of jaws, neuromuscular or neurotic disorders, drug addicts, uncooperative, unwilling and handicapped were excluded. Results: The females were 112(54.11%) and males were 95(45.89%). The mean age of the study was 51.94±11.62 years. The mean duration of wearing RPDs was 2.99±1.63 years. The mean OHIP-14 Score was 23.2±7.16. The OHIP score among females were more (24.27±7.17) than males (21.94±6.989). The satisfaction with RPDs wearing increased as the duration of denture use increase (P=0.005). Comparison of OHIP-14 score among age groups showed that patients satisfaction with RPDs wearing was not affected by age of the patient (P=0.191). Conclusion: Our mean OHIP-14 Score is lower than international studies showing less satisfaction with removable partial denture. The females were more satisfied with wearing RPDs than males. The satisfaction with RPDs wearing increased as the duration of denture use increase. Patient’s satisfaction with RPDs wearing was not affected by their age.